El estrés laboral y el desempeño de los trabajadores de Mega Inmobiliaria Mega Vip Cia. Ltda. - Ponce Lema, Luis Gabriel (2024)
Work stress and employee performance in Mega Inmobiliaria Mega Vip Cia. Ltda., in the city of Riobamba, are very important components within the company. These two variables act one upon the other, so we must consider their influence on the correct functioning of the company. In this research, general and specific objectives and hypotheses were raised that contribute to the theoretical framework where the study variables are described. This knowledge provides the foundation for a proposal for strategies that lower the levels of work stress when evaluating workers' performance. A hypothetical-deductive methodology was used to raise and verify the hypothesis from the collection of statistical data, proceed to analyze them, facilitate the study of the research phenomenon, and provide a solution to the problem raised in the research work. The survey of Mega Inmobiliaria Mega Vip Cia. Ltda. Workers were used as a collection technique, allowing us to determine the stress levels within the company. The results obtained show a lack of clarity in the company's goals and mission, the absence of control over activities, the lack of collaboration in the team, and the lack of support from the supervisor, which contributes to a stressful environment that can reduce efficiency and job satisfaction.